Evaluating m-learning applications for children's early education: a parental point of view / Nor Malini A. Hamid - A. Hamid, Nor Malini (2012)
Teaching and learning begins from home from the very start of a child's journey from infancy to adulthood. Recent advancement in handheld devices has seen the potential in assisting the learning process of young children, apart from the element of fun and attractiveness. This study was conducted to know parents' point of view when using mobile devices to deliver early education to their children. Two methods were used for this study which is qualitative and quantitative evaluation. For the quantitative study, questionnaires were distributed to parents and for the qualitative study interview with parents and observation on children using the device was done. The results show that although many parents are still not aware on mobile learning (m-learning) but theoretically they believe that m-learning can help improve ways of delivering early learning. Also children also prefer learning using mobile applications (mobile apps) compared to using books and they will learn longer with it. Finally there should be more mobile app downloaded to the devices since children will change the apps when they feel bored or give up.